1977
DOI: 10.1126/science.196.4292.885
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Influence on Blue-Green Bloom Sequence in a Eutrophic Lake

Abstract: The bloom sequence in a eutrophic lake, Linsley Pond, over a period of 3 years is correlated to the effects of cell-free filtrates of dominant blue-green algae on both their successors and their predecessors. There is unbroken correspondence between the effects of heat-labile probiotic and antibiotic filtrates and the rise and fall of bloom populations in situ. All organisms in vitro were axenic or unialgal (bacterized) isolates from Linsley Pond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(159 citation statements)
references
References 7 publications
2
157
0
Order By: Relevance
“…Considering that some allelochemicals are inducible and their production controlled by stress or other environmental factors (see Sections 1.A and V.A), we should expect a changing susceptibility of target organisms to allelopathically active species within one habitat. Further, the studies by Keating (1977Keating ( , 1978 showed that allelopathy might explain phytoplankton succession within one lake. Thus, not only spatial concems (same or different original habitat of interfering species) but also temporal aspects (climax of stressors, seasonal succession of species) need reference.…”
Section: B Suitable Target Organisms and Impact Of Stressors On Allementioning
confidence: 99%
See 1 more Smart Citation
“…Considering that some allelochemicals are inducible and their production controlled by stress or other environmental factors (see Sections 1.A and V.A), we should expect a changing susceptibility of target organisms to allelopathically active species within one habitat. Further, the studies by Keating (1977Keating ( , 1978 showed that allelopathy might explain phytoplankton succession within one lake. Thus, not only spatial concems (same or different original habitat of interfering species) but also temporal aspects (climax of stressors, seasonal succession of species) need reference.…”
Section: B Suitable Target Organisms and Impact Of Stressors On Allementioning
confidence: 99%
“…First, pelagic algae and cyanobacteria may use allelopathically active compounds to outcompete other species, to gain dominance over predecessors, or infiuence the type of conspecifics and successors. Fundamental studies have been done by Keating (1977Keating ( , 1978 on allelopathy and the cyanobacterial dominance in eutrophic lakes. Allelopathy in pelagic environments depends on sufficient production and excretion of allelopathically active compounds into the water and their effective distribution to reach target species at active concentrations.…”
Section: A Differences Between Terrestrial and Aquatic Habitatsmentioning
confidence: 99%
“…The growth rate of Aphanizomenon surpassed that of Anabaena but abruptly ceased. The production of allelopathically-active compounds, whose effects correlate with cell density, could provide a plausible explanation for this pattern (Keating, 1977 ;Flores & Wolk, 1986 ;Bagchi, Chauhan & Marwah, 1993). Some strains of Anabaena are known to release such growth-inhibitors, and some of these compounds interfere with photosynthetic electron transport and are presumed to be more inhibitory under lightlimited conditions (Von Elert & Ju$ ttner, 1996).…”
Section: Light-limited Growth Of Diazotrophsmentioning
confidence: 99%
“…Even before the Vienna botanist Hans Molisch coined the term allelopathy to describe biochemical interactions among plants and between plants and microorganisms (Molisch, 1937), some studies reported negative effects of one primary producer on another not related to resource competition (Harder, 1917;Akehurst, 1931), and multiple studies followed (e.g., Pratt et al, 1944;Keating, 1977). Although by its original definition, stimulatory and inhibitory allelopathic effects might occur, most studies report negative interactions.…”
Section: Introductionmentioning
confidence: 99%